Impact of Audit Committee Attributes and Liquidity on Sustainability Reporting - Waseem, Fareeha; Hamid, Sara Zahid; Javed, Abeera (Audit and Accounting Review, 2024)
This research aims to investigate the impact of audit committees, liquidity, leverage, and return on assets (ROA) on the sustainability reporting of firms. Additionally, the study conducts a comparative analysis of sustainability reporting practices between Pakistani food companies and BRICS food companies. The collected data included 360 samples of food companies for the period 2017-2022, including data from Pakistan and the top five (05) emerging market economies comprising BRICS, namely Brazil, Russia, India, China, and South Africa. Secondary data was employed in this study, utilizing information from sustainability reports and annual reports. Logistic regression analysis was used to analyze the results. The findings indicate that audit committee members and independent audit committee members significantly impact sustainability reporting, while audit committee meetings, board meetings, and liquidity do not. These findings provide valuable insights for investors seeking to understand the determinants of sustainability reporting, as well as for researchers exploring the interplay between corporate governance and financial performance in emerging markets. Furthermore, this study contributes to the literature by highlighting the relationship between audit committees, liquidity, and sustainability reporting in the context of the food sector in Pakistan and BRICS countries.